2019
DOI: 10.3389/fmicb.2019.01537
|View full text |Cite
|
Sign up to set email alerts
|

Interactome of Glyceraldehyde-3-Phosphate Dehydrogenase Points to the Existence of Metabolons in Paracoccidioides lutzii

Abstract: Paracoccidioides is a dimorphic fungus, the causative agent of paracoccidioidomycosis. The disease is endemic within Latin America and prevalent in Brazil. The treatment is based on azoles, sulfonamides and amphotericin B. The seeking for new treatment approaches is a real necessity for neglected infections. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is an essential glycolytic enzyme, well known for its multitude of functions within cells, therefore categorized as a moonlight protein. To our k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 99 publications
2
5
0
Order By: Relevance
“…These data provide the first large-scale identification of exoantigens of Paracoccidioides species. Some of these exoantigens have already been identified and described as antigens of pathogenic fungi, such as formamidase (Borges et al, 2005(Borges et al, , 2010, dihydrolipoyl dehydrogenase (Landgraf et al, 2017), HSP60 (Izacc et al, 2001;Cunha et al, 2002), HSP70 (Bromuro et al, 1998;Bisio et al, 2005), serine protease (Parente et al, 2010;Lacerda Pigosso et al, 2017), and isocitrate lyase (Cruz et al, 2011;Silva et al, 2019). This demonstrates the robustness of method used in our immunoproteomics analyses.…”
Section: Discussionsupporting
confidence: 54%
“…These data provide the first large-scale identification of exoantigens of Paracoccidioides species. Some of these exoantigens have already been identified and described as antigens of pathogenic fungi, such as formamidase (Borges et al, 2005(Borges et al, , 2010, dihydrolipoyl dehydrogenase (Landgraf et al, 2017), HSP60 (Izacc et al, 2001;Cunha et al, 2002), HSP70 (Bromuro et al, 1998;Bisio et al, 2005), serine protease (Parente et al, 2010;Lacerda Pigosso et al, 2017), and isocitrate lyase (Cruz et al, 2011;Silva et al, 2019). This demonstrates the robustness of method used in our immunoproteomics analyses.…”
Section: Discussionsupporting
confidence: 54%
“…MET 120 and ASN 121 are contact residues between ICL and FBA1, PGK, PK, GAPDH and ENO. The fact that those proteins belong to the glycolytic pathway and since they share similar contact residues with ICL, reinforce the idea of the existence of a glycolytic metabolon in P. lutzii [84]. GLN .…”
Section: P Lutzii Icl Has Several Regions Of Interaction Interfacesupporting
confidence: 59%
“…MET 120 and ASN 121 are contact residues between ICL and FBA1, PGK, PK, GAPDH and ENO. The fact that those proteins belong to the glycolytic pathway and since they share similar contact residues with ICL, reinforce the idea of the existence of a glycolytic metabolon in P. lutzii [ 84 ]. GLN 502 and LYS 503 establish contact between ICL and partners in ENO, MDH, MCS and MCD, while LYS 513 of ICL interacts with PK, MDH, ECH and ACA.…”
Section: Resultsmentioning
confidence: 72%
“…We identified GAPDH S-nitrosylated (SNO-GADPH) in all conditions analyzed (Supplementary Table S1). In GAPDH interactome analyzes was observed that SNO-GAPDH can interact with several P. lutzii proteins, such as acyl CoA dehydrogenase, argininosuccinate synthase, aldehydedehydrogenase, rad24, among others (Silva et al, 2019). GAPDH is well-known for its role in cytosolic glycolysis (Tristan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%